Interplay of traditional knowledge and adaptive capacity in climate change adaptation of small-scale fishers in central Terengganu, Malaysia - Yamin, Liyana; Kuo, Ting-Chun; Aziz, Nazli (Frontiers in Marine Science, 2025)
IntroductionClimate change is a major threat to small-scale fishers and coastal population of Malaysia, especially a significant population relies on the industry. However, records on adaptation capacity of these communities remains limited.MethodThis study investigated the perceived risks of climate change among 136 small-scale fishers in Terengganu, Malaysia and the influence of traditional knowledge on adaptive capacity to climate change. Data were collected from five villages in the coastal area of central Terengganu, Malaysia, using a snowball sampling method.ResultsThe respondents identified three primary climate hazards: stronger monsoonal winds and larger waves (noted by 95% of the respondents), more intense weather (91%), and erratic rainfall patterns (91%). The majority of fishers attributed climate change to natural variability (90%) and the anger of God (85%). Of the five dimensions of adaptive capacity, flexibility was identified as the weakest. A structural equation model was employed to analyze the relationship between traditional knowledge and adaptive capacity. The results revealed that spiritual practice was the most significant component of traditional knowledge and subsequently, in general, had a significant impact on the adaptive capacity of fishers.DiscussionThe study highlighted the negative perception by fishers due to the neglect of their concerns by government. To enhance the adaptive capacity of small-scale fishers, national agencies and local fishing associations must actively engage with these effective adaptation strategies.